Fluorescence of 6-methoxyquinoline, quinine, and quinidine in aqueous media - Capomacchia, Anthony C. (1974)
The absorption and fluorescence spectra of 6-methoxy-quinoline, quinine, and quinidine were studied as a continuous function of pH. 6-Methoxyquinoline is a stronger base in the lowest excited singlet state, as reflected by the pH dependence of its fluorescence. The latter is used to calculate the rates and equilibria of proton exchange in the excited state. Quinine and quinidine, however, do not protonate during the lifetimes of their excited states, an observation attributed to the lower basicity of their aromatic heterocyclic nitrogen than that in 6-methoxyquinoline. The differences in basic properties between the alkaloids and 6-methoxyquinoline are employed to infer the ketonic character of the quinolinemethanol group of the alkaloids and the existence of an intramolecular hydrogen bond in quinine but not in quinidine.